EFEKTIVITAS PELATIHAN SELF-TALK UNTUK MENINGKATKAN HARGA DIRI REMAJA KORBAN BULLYING (Studi pada Siswa SMP X Pasar Minggu) - Marhani, Isnaeni; Sahrani, Riana; Monika, Sesilia (Universitas Islam Negeri Alauddin Makassar, 2018)
Abstract: Adolescents who are unable to adapt in school environments are more likely to get bullying from other, more dominant or more popular students. Bullying makes teenagers difficult to actualize themselves, concentrate on learning, always feel insecure, and have low self-esteem. Teenagers with low self-esteem will believe that what the bully says about him is true and start blaming himself for being weak, not beautiful, or useless. Low self-esteem can be increased one of them through self-talk techniques that aim to deny irrational thinking and encourage the emergence of healthy thinking by saying positive sentences. Bullying behavior by peers is still common in junior high school, so some students become more quiet, crying in school, avoiding bullying, asking to move classes, to choose to change schools. This research was conducted to find out the effectiveness of self-talk training to increase the self-esteem of bullying students in SMP X. This study used experimental design involving 10 participants aged 14 to 16 years. The researchers used the Self-Estimation tool developed by Utomo (2011) as a pre-test and post-test. Based on different test with paired sample t-test on gain score of self esteem obtained mean value 14.80 (SD = 3.271) and t = 7.020, p <0.01. Thus, self-talk training is effective to increase the self-esteem of bullying teenagers.